Сказочные повести - Прокофьева Софья Леонидовна (Школьная библиотека, 2012)
Экземпляры: Ф. 3 (20201020) / Инвентарный номер: 43811 / Цена: 118.80 / Сис.шифр: 84(2 РОС=Рус)6 / Авт.знак: П 80 / ГРНТИ: 17.82 / ББК: 84(2 РОС=Рус)6